Neoadjuvant Immunotherapy Combined Chemotherapy Followed by Surgery Versus Surgery Alone for Locally Advanced Esophageal Squamous Cell Carcinoma: A Propensity Score-Matched Study - Hong, Zhi-Nuan; Weng, Kai; Peng, Kaiming; Chen, Zhen; Lin, Jihong; Kang, Mingqiang (Frontiers in Oncology, 2021)
Abstract Background Combination of neoadjuvant immunotherapy and chemotherapy (nICT) is a novel treatment for locally esophageal cancer squamous cell carcinoma (ESCC). This study aimed to evaluate the potential benefit of nICT on surgery safety by comparing short-term outcomes between surgery alone group and nICT followed surgery group. Methods A retrospective analysis was performed to identify patients (from January 2017 to July 2021) who underwent surgery for ESCC with or without nICT. A propensity score matching（PSM）comparison (1:1) was conducted to reduce selection biases and balance the demographic and oncologic characteristics between groups. Results After PSM, the nICT group (n=38) was comparable to the surgery alone group(n=38) in the following characteristics: age, sex, BMI, ASA status, smoking, tumor location, lymph node resection, clinical stage, anastomotic location, surgical approach and surgical approach. The operation time and incidence of postoperative pneumonia in nICT group were higher than those in control group(P<0.05). However, other complications and major complications were comparable between the two groups. There was no significant difference between the two groups in intraoperative blood loss, ICU stay time, postoperative hospital-stay and hospitalization cost. The 30-day mortality, 30-day readmission, and ICU readmission rates were also similar in the nICT and control groups. In nICT group, the pathological complete response rate in primary tumour was18.4%, and the major pathological response rate in tumor was 42.1% Conclusions Based on our preliminary experience, nICT followed by surgery is safe and effective with acceptable increased operation risk, manageable postoperative complications and promising pathological response. Further multicenter prospective trials are needed to validate our results.